Nrf2 sensitizes prostate cancer cells to radiation via decreasing basal ROS levels. (2nd January 2015) - Liu, Min; Yao, Xu‐Dong; Li, Wei; Geng, Jiang; Yan, Yang; Che, Jian‐Ping; Xu, Yun‐Fei; Zheng, Jun‐Hua
Abstract Androgen deprivation therapy (ADT) was reported to lower basal ROS level in prostate cancer (PCa) and to sensitize PCa to radiation. We aimed to seek for the underlying molecular mechanism and to develop novel additive treatments to ADT in this regard. We simulated human androgen milieu in vitro and tested the ROS level in PCa cells undergoing ADT. We also tested the Nrf2 level in PCa cells with or without ADT. Genetic and pharmaceutical upregulation of Nrf2 was applied in vitro and in vivo in transgenic adenocarcinoma of the mouse prostate (TRAMP) mice with or without castration to investigate whether Nrf2 overexpression supplemented the effect of ADT in PCa. We first discovered that androgen deprivation increased basal ROS level in PCa cells with AR expression. We then found that genetic Nrf2 upregulation lowered basal ROS similar to ADT. Also, SFN sensitized PCa cell to radiation via upregulation of Nrf2. We then found that Nrf2 level in control TRAMP groups was lower than castration or SFN groups. The SFN treated TRAMP mice showed similar level of Nrf2 to castration. Genetic and pharmaceutical upregulation of Nrf2 lowered the ROS in PCa cells and sensitized PCa cells to radiation similar to ADT, implicating possible administration of SFN in place of ADT for PCa patients requiring radiotherapy. © 2015 BioFactors, 41(1):52–57, 2015